The Effect Of Online Learning On Students' Learning Motivation At Shailendra Sma Palembang - Eka Octa Nuryani; Muhammad Ferdiansyah; Nurlela Nurlela (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
This study aims to determine the effect of online learning on student motivation at SMA Shailendra Palembang. In this study, the research design used was ex post facto research with a quantitative approach. This research was conducted on high school students Shailendra. The research sample used was 106 students. The data analysis technique used in this research is quantitative analysis, namely data analysis using statistical calculations to test the hypotheses that have been proposed through regression analysis with the help of the SPSS 25 for windows program. The results showed that there was a positive effect of online learning on students' learning motivation at SMA Shailendra Palembang, hypothesis testing showed that the online learning variable (Y) had a tcount value of 10.076 which was greater than the ttable value of 1.983 with a significance level of 0.000 which was smaller than 0. ,05, then Ha is accepted and Ho is rejected, the coefficient of determination shows the magnitude of the influence or contribution of online learning on student learning motivation at SMA Shailendra Palembang is 49.4% and the remaining 50.6% of student learning motivation is influenced by other factors outside of learning by online.